1987
DOI: 10.1123/jsp.9.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Competitive State Anxiety Inventory-2 Subscale Scores and Pistol Shooting Performance

Abstract: This study examined whether linear or curvilinear (inverted-U) relationships exist between Competitive State Anxiety Inventory-2 subscale scores and pistol shooting performance in a paradigm that addressed previous design, methodological, and data analysis problems. Officers (N = 39) from the University of Illinois Police Training Institute served as subjects and participated in a pistol shooting competition. Each subject shot on five separate occasions, immediately after completing the CSAI-2 (Martens, Burton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
3
8

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(91 citation statements)
references
References 11 publications
5
75
3
8
Order By: Relevance
“…Researchers have demonstrated that a wide range of emotions are associated with changes in performance levels (e.g., Burton, 1988;Gould, Petlichkoff, Simons, & Vevera, 1987;Hanin, 2000;Hanin & Syrjä, 1995a;Hanin & Syrjä, 1995b;Jones, Mace, & Williams, 2000). Recently, Botterill and Brown (2002), Hanin (2000), Lazarus (2000b), and Vallerand and Blanchard (2000) have all outlined the mechanisms by which emotions may influence performance.…”
Section: How Emotions Impact Sport Performancementioning
confidence: 99%
“…Researchers have demonstrated that a wide range of emotions are associated with changes in performance levels (e.g., Burton, 1988;Gould, Petlichkoff, Simons, & Vevera, 1987;Hanin, 2000;Hanin & Syrjä, 1995a;Hanin & Syrjä, 1995b;Jones, Mace, & Williams, 2000). Recently, Botterill and Brown (2002), Hanin (2000), Lazarus (2000b), and Vallerand and Blanchard (2000) have all outlined the mechanisms by which emotions may influence performance.…”
Section: How Emotions Impact Sport Performancementioning
confidence: 99%
“…Their approach to performance assessment followed suggestions from sport psychology to include process measures that may reflect the task complexity of different sports (e.g. Gould, Petlichkoff, Simons, & Vevera, 1987). As Weinberg (1990) had noted, focusing solely on performance outcome (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmamız bulgularına benzer şekilde, Gould, Petlichkoff, Simon ve Vevera'nın (1987), atıcılarla yapmış oldukları araştırmada performansla kaygı arasındaki ilişkinin bilişsel olarak doğrusal-negatif olduğunu göstermiştir. Baskı altında çalışan polislerin, yüksek kaygı düzeyinde yapılan atış başarısının düşük kaygı düzeyinde yapılan atış başarısına göre daha düşük olduğu tespit edilmiştir (Gould, Petlichkoff, Simons, ve Vevera, 1987; R. Daha önce belirtildiği üzere kalbin kasılma ve gevşemesi olarak adlandırılan kardiyak döngü süresince tüm vücutta gerçekleşen küçük sarsıntıların atış sporlarında el-göz koordinasyonu gerektiren bir dizi hareketin yapılmasında problem olarak ortaya çıkmaktadır. Bu nedenle atış sırasındaki yüksek kalp atım hızının atış performansını olumsuz etkilediği tespit edilmiştir (Hall, 2010;Helin et al, 1987;İpek Eroğlu Kolayiş ve Emel Mimaroğlu, 2008;Konttinen et al, 1998;Kruse, Ladefoged, Nielsen, Paulev, ve Sorensen, 1986;Wang ve Landers, 1986) Atış sırasında artan kalp atım hızının kassal aktivite sonucu artan enerji tüketimi nedeniyle değil psikolojik nedenlerden kaynaklı olduğu düşünülmektedir.…”
Section: Discussionunclassified